2022
DOI: 10.1002/cbf.3740
|View full text |Cite
|
Sign up to set email alerts
|

ATG5: A central autophagy regulator implicated in various human diseases

Abstract: Autophagy, an intracellular conserved degradative process, plays a central role in the renewal/recycling of a cell to maintain the homeostasis of nutrients and energy within the cell. ATG5, a key component of autophagy, regulates the formation of the autophagosome, a hallmark of autophagy. ATG5 binds with ATG12 and ATG16L1 resulting in E3 like ligase complex, which is necessary for autophagosome expansion. Available data suggest that ATG5 is indispensable for autophagy and has an imperative role in several ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 210 publications
0
14
0
Order By: Relevance
“…OPTN is an autophagy receptor that is associated with many human diseases closely related to autophagy, such as rheumatoid arthritis, osteoporosis and nephropathy 33 . ATG5, a classical autophagic core protein, is essential in autophagic expression 34 , and experimental ndings by zhu 35 and others found that ATG5 knockdown attenuated autophagy-induced iron death. SOD1 is an anti-oxidant metalloenzyme catalyzing the dissociation of superoxide anion radicals to produce oxygen and hydrogen superoxide.…”
Section: Discussionmentioning
confidence: 95%
“…OPTN is an autophagy receptor that is associated with many human diseases closely related to autophagy, such as rheumatoid arthritis, osteoporosis and nephropathy 33 . ATG5, a classical autophagic core protein, is essential in autophagic expression 34 , and experimental ndings by zhu 35 and others found that ATG5 knockdown attenuated autophagy-induced iron death. SOD1 is an anti-oxidant metalloenzyme catalyzing the dissociation of superoxide anion radicals to produce oxygen and hydrogen superoxide.…”
Section: Discussionmentioning
confidence: 95%
“…Lamp2 is associated with the lysosomal membrane, and the reduction of Lamp2 will lead to lysosomal dysfunction [30]. Autophagyrelated gene 5 (Atg5), essential for autophagic vesicle formation and autophagosomes maturation, has also been proven to be a regulator of autophagic ux [31]. Compared with the Ad.GFP + NC + H 2 O 2 group, overexpression of Sirt1 alone could increase autolysosomes by increased expressions of Rab7 and Lamp2, rather than Atg5.…”
Section: Discussionmentioning
confidence: 99%
“…The ATG12–ATG5–ATG16L conjugate plays a role in both binding and closure processes, it was found that ATG12 was catalyzed by ATG7 to bind to ATG5. This conjugate then interacts with other autophagy associated proteins, primarily ATG8, to form complexes that regulate autophagy protein formation (Changotra et al, 2022). The closure process, which represents the formation of a complete two‐membrane autophagosome, is the process by which the phagosome will need to be completely surrounded by the isolated material.…”
Section: Autophagy In Hccmentioning
confidence: 99%